Event-related theta and alpha oscillations under emotional stimuli: an MEG study. Issue 1 (2nd January 2017) - Hayashi, Takuto; Mizuno-Matsumoto, Yuko; Kohri, Shimpei; Nitta, Yoshinori; Tonoike, Mitsuo
Abstract: The present study investigates phase-locked and non-phase-locked brain responses in the theta and alpha frequency bands. A 122-ch whole-head magnetoencephalogram (MEG) was recorded continuously during emotional audio-visual stimuli. Compared to the pre-stimulus, the phase-locked theta activity increased over the left centro-temporal cluster at 400 − 500 ms in the pleasant stimuli and at 100 − 500 ms in the unpleasant stimuli. These activities were stronger with pleasant and unpleasant stimuli compared to relaxed stimuli. These results indicate that an emotionally high arousal state might induce the phase-desynchronized brain activity in the theta frequency band soon after the onset of the stimuli.